Investigation of structural and morphological insights of nanostructured layered double hydroxides: catalytic activity in aldol condensation - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Thakare, Sanjay R. (Journal of Porous Materials, 2024)
Layered double hydroxides (LDHs) materials finds extensive applications in numerous fields such as medical science, industrial sector, agriculture and food, catalysis, polymers, nanotechnology, etc. The LDHs properties (structural, textural, morphological, spectroscopic and theoretical insights) can be design for achieving required materials for particular application in scientific areas. In the current investigation, we have synthesized mesoporous nanostructured LDHs materials via microwave, sonication and stirring method. The nanostructured LDHs was scientifically characterized by various physico-chemical techniques like XRD, N2 sorption, TGA, solid state one-dimensional 27Al magic angle spinning NMR spectroscopy, XPS, Raman Spectroscopy, FT-IR, ICP-OES, Electron Microscopy (SEM, FE-SEM, TEM and HR-TEM), EDX, elemental analysis, etc. On the basis of experimental study, it can be evidently witnessed that nanostructured LDHs materials was formed with good crystalline mesoporous nature. Solid state 27Al NMR showed single and sharp 27Al NMR signal at chemical shift value of + 1.4 ppm, strongly suggesting the presence of octahedral (Oh) AlO6 coordination site in all as-synthesized LDHs. Microwave and sonication techniques furnishes regularly dispersed well-developed flower-shaped nanocrystals however, stirring method gives mostly agglomerated nano-sized platelets. The mechanistic insights for the fabrication of nanostructures LDHs via microwave, sonication and stirring process were also highlighted. The different LDHs materials were utilized in the aldol condensation reaction of furfural with acetone for understanding structure-activity correlation. Microwave and sonication methodologies can be further exploited for the synthesis of many other inorganic-organic nanocomposites materials with stable and good dispersion of nanocrystals in addition to desired morphology and catalytic activity.
Keywords: Aldol condensation; catalysis; Flower-shaped nanocrystals; layered double hydroxides; Microwave and sonication techniques; Nanostructured materials

Synergistic effect of acidic-basic features of copper-doped layered double hydroxides nanocatalysts in valorization of biomass-derived furfural to biofuels - Gode, Nilesh G.; Nagpure, Atul S.; Rewatkar, Suresh B.; Bhagat, Shailesh K.; Deshmukh, Ganpat D.; Saini, Ajay (ChemPlusChem, 2025)
Valorization of biomass-derived chemicals into high-quality compounds and biofuels is enormously fundamental to diminish dependence on fossil-based resources. Furfural is a bio-based valuable compound which can be proficiently upgraded to 4-(2-furyl)-3-buten-2-one (FAc) and 1,4-pentadiene-3-one, 1,5-di-2-furanyl (F 2 Ac) via aldol condensation of furfural with acetone. In the present work, efficient Cu-doped Mg-Al layered double hydroxides (LDH) nanocatalysts are fabricated by coprecipitation and are exploited for furfural conversion to obtained FAc and F 2 Ac. The structure-activity relationship is scrutinized by characterizing fresh and spent nanocatalysts via numerous techniques. The good correlation between the amount of weak acidic-weak basic catalytic sites and nanocatalysts performance is established. The superior performance of Cu-0.1 nanocatalyst (Cu-content = 1.85 wt%) in aldol condensation is attributed to the presence of optimum weak acidic sites (0.21 mmol g-1) and weak basic sites (0.36 mmol g-1), synergistic acidic-basic effect, nano-sized Cu(OH) 2 nanoparticles (1.6 nm), high BET surface area (181 m2 g-1), and mesoporous architecture of material. Cu-0.1 nanocatalyst delivered 98% FAc selectivity with 100% furfural conversion at 85 degrees C. Furthermore, at 100 degrees C, the nanocatalyst gives 55% F 2 Ac selectivity with 73% furfural conversion. The catalyst displays good recyclability (7 recycles) and stability. Plausible mechanistic pathway for transformation of furfural to FAc and F 2 Ac is proposed.
Keywords: Aldol condensation; biofuels; biomass valorization; nanocatalysis; synergistic effect

Upgradation of biomass-derived furfural by nanostructured layered double hydroxides: Influence of stirring rate on structural features of materials - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Deshmukh, Ganpat D.; Saini, Ajay (Inorganic Chemistry Communications, 2025)
The proficient conversion of biomass-derived compounds into the high-quality platform chemicals and bio-fuels is enormously imperative to decrease dependence on fossil feedstock. Furfural is a significant bio-based chemical which can be efficiently converted to valuable 4-(2-furyl)-3-buten-2-one (FAc) via aldol condensation. In this work, we have developed prominent layered double hydroxides (LDHs) catalysts for mild aldol condensation of furfural and acetone to acquired high performance with admirable FAc selectivity. Various nanostructured Mg-Al LDHs were synthesized through co-precipitation procedure under different stirring rate conditions. The structural, morphological and optical attributes of materials as well as recyclability aspect and structure-activity relationship was examined by characterizing the fresh and spent catalysts via numerous techniques (XRD, N2 sorption, DLS, CO2-TPD, NH3-TPD, FT-IR, UV-Visible spectroscopy, TGA, SEM, TEM, ICP-OES, 27Al NMR spectroscopy, XPS, Raman spectroscopy, etc). Several reaction parameters were also optimized. Among the catalysts tested, LDH-1200 catalyst exhibits outstanding performance by delivering 100% furfural conversion with 99% FAc selectivity. Moreover, catalyst illustrates excellent recyclability and stability. The mechanistic insight for aldol condensation was also investigated by monitoring the intermediates at different stages and intervals during the course of the reaction. This study confirms that stirring rate has significant influence on physico-chemical attributes of materials and the amount of weak basic sites plays imperative role in catalytic performance.
Keywords: Aldol condensation; Biomass-derived compounds; Flower-shaped nanocrystals; heterogeneous catalysis; Nanostructured mesoporous LDH